The role of workplace accommodations in the employment of people with disabilities - Priyanka Anand; Purvi Sevak (IZA Journal of Labor Policy, 2017)
We explore the role of workplace accommodations in reducing employment barriers and improving the employment of people with disabilities. We do so using data from the 2015 Survey of Disability and Employment on people with disabilities who applied for vocational rehabilitation services in three states. The results show that at least one third of nonworking people with disabilities reported employment barriers that could be addressed by workplace accommodations, such as lack of transportation and an inaccessible workplace. We also find that receiving certain types of workplace accommodations, such as help with transportation, flexible work schedules, or a personal care attendant, is positively correlated with being employed at the time of the survey. Finally, people who are in poor health or have physical disabilities were more likely to perceive workplace inaccessibility as a barrier but less likely to have received accommodations in their current or most recent job. This suggests that people with these characteristics may be good candidates to target for greater access to workplace accommodations.
Keywords: I1; J2; J32; 330; Employment; Disability; Labor force participation; Workplace accommodations